Pelatihan MS Office bagi Guru SD Masehi Kadu Eta Desa Kadu Eta - Friden Elefri Neno; Andreas Ariyanto Rangga; Katarina Yunita Riti (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The rapid development of technology has greatly assisted human work in various fields, including education. One tangible outcome of technological progress is the availability of Microsoft Office applications, which consist of Microsoft Word, Microsoft Excel, and Microsoft PowerPoint. Microsoft Word functions as a word processing software that allows users to create, edit, and format documents, while Microsoft Excel is used for managing numbers and data, and PowerPoint plays an important role in preparing engaging presentations. However, the teachers at SD Masehi Kadu Eta are not yet able to operate Microsoft Word, Excel, and PowerPoint optimally, as the school has never conducted any specific training. Therefore, this community service program focused on providing training on how to utilize Microsoft Office for teachers at SD Masehi Kadu Eta. The training aimed to improve teachers’ knowledge and skills in using information technology, particularly in operating Microsoft Word, Excel, and PowerPoint. Through this program, teachers gained not only new experiences but also basic skills that can support their daily tasks, such as preparing school administration documents, creating reports, and developing more systematic teaching materials. The results of the program showed that the training provided significant benefits. Teachers demonstrated strong enthusiasm, actively participated in every session, and showed improvement in their understanding of Microsoft Office applications. They also expressed their expectations for similar activities to be carried out regularly so that their skills could continue to improve and better equip them to face the ongoing development of information and communication technology in the future.